The Relationship of The Discipline And Motivation On Performance Employees - Magani, Yosephin Intan; L.Tobing, Suzanna Josephine (Fundamental Management Journal, 2018)
A company certainly has a goal to develop its business, one of them by having a professional human resources and competent in the field. To achieve the company's goals, one of the things employee must do is apply the rules and regulations. In addition to building discipline, the role of a leader is also very important to give confidence to employees in carrying out their duties and pay attention to employees who complete the work exceeds the established standards. The quality of the work becomes an evaluation for the leaders and employees in the division. Discipline and motivation are closely related to employee performance for the progress of a company.Keywords : Company, Human Resources, Employee Performance